The Sima de los Huesos Middle Pleistocene hominin site (Burgos, Spain). Estimation of the number of individuals - Bermúdez de Castro, José María; Martínez, Ignacio; Gracia‐Téllez, Ana; Martinón‐Torres, María; Arsuaga, Juan Luis (Anatomical record (Hoboken, N.J. : 2007), 2021)
After 34 years of research and findings in the Middle Pleistocene site of the Sima de los Huesos (SH) of the Sierra de Atapuerca (Burgos, Spain), we present an update of the estimation of the number of individuals (ENI) identified in the SH hominin assemblage. The last ENI, published in 2004, was 28. Although the number of specimens recovered has almost doubled since then and more complete information is now available, this new analysis suggests that the ENI is 29. Some individuals are still represented by only one or a few teeth and the upper and lower jaws of various individuals have not been completed. We suggest that the amateur cavers, who accessed the SH site for years looking for bear fossils, destroyed a significant number of hominin fossils. Despite this, we have a good picture of the group of hominins represented in the SH assemblage. Because complete corpses were accumulated in SH and it is a closed cavity, it is expected that a significant number of hominin fossils remains to be discovered. According to the previous estimates, the representation of females is greater than that of males. However, the observed sex ratio is not significantly different from the 1:1 ratio. With the exception of the possible presence of a child individual, most of the remaining 28 individuals are teenagers or young adults (24/28 = 0.857). The ages of death of SH hominins appear to conform to a catastrophic profile.